Expansion of CD16-Negative Natural Killer Cells in the Peripheral Blood of Patients with Metastatic Melanoma - Shernan G. Holtan; Douglas J. Creedon; Michael A. Thompson; Wendy K. Nevala; Svetomir N. Markovic (Clinical and Developmental Immunology)
Altered natural killer (NK) cell function is a component of the global immune dysregulation that occurs in advanced malignancies. Another condition associated with altered NK homeostasis is normal pregnancy, where robust infiltration with CD16− CD9+ NK cells can be identified in decidual tissues, along with a concomitant expansion of CD16− NK cells in the maternal peripheral blood. In metastatic melanoma, we identified a similar expansion of peripheral blood CD16− NK cells (median 7.4% in 41 patients with melanoma compared with 3.0% in 29 controls, P<.001). A subset of NK cells in melanoma patients also expresses CD9, which is characteristically expressed only on NK cells within the female reproductive tract. Expansion of CD16− NK cells was associated with elevated plasma transforming growth factor-beta (TGF-β levels (median 20 ng/ml, Spearman's ρ=0.81,P=.015)). These findings suggest the possibility of exploring anti-TGF-β therapy to restore NK function in melanoma.